Risk hotspot of chemical accidents based on spatial analysis in Ulsan, South Korea. (March 2020) - Yu, Hangnan; Lee, Woo-Kyun; Sohn, Jong Ryeul
Highlights: Risk hotspot of chemical accidents was detected in the building-intensive region. Clustered aging factories have created favorable conditions for risk of accidents. Harsh living environment around chemical plants induced health and economic issues. Chemical accidents will be further enhanced by neglect of safety management training. Abstract: The chemical industry is one of the major industries driving the Korean economy. However, increased chemical use accompanied by obsolete equipment and careless management has promoted the occurrence of chemical accidents. Therefore, to develop a preventive planning that can minimize human injury and economic losses caused by possible accidents, chemical risk hotspots should be identified. This study proposed a methodology based on geographical information system (GIS) and remote sensing (RS) to map risk hotspots in Ulsan, South Korea. Considering causes and effects of accidents, four categories were analyzed from a physical and social perspective: source of pollution (chemical plants and accidents), catalyst of pollution (wind speed and land surface temperature), receptor (population and residential area), and coping ability (distance to the nearest hospital, fire station, and main road). The results showed that the chemical risk hotspot covers at least 16 dongs of Ulsan and involves approximately 400, 000 citizens, which represent 38% of the city's population. In addition, issues such as aging factories, contaminated environments, and lack of safety education further increase the chemical risk. Therefore, regular safety monitoring of chemical plants and their surroundings is essential to reduce future risks in this area.